The Influence Of Certain Geologic And Geotechnical Factors On Coal Mine Floor Stability - A Case Study - Introduction - Robert C. Speck (International Conference on Ground Control in Mining, 1981)
Floor heave or deformation of the mine floor into the mine opening is a problem which has plagued coal mines in this country and others. In mining areas where room and pillar mining is practiced, floor heave generally occurs when the stress applied to the floor material by a coal pillar exceeds the bearing capacity of the floor strata. When the floor strata beneath the coal pillar fail, the pillar moves downward and displaces the material under it. This material, in turn, moves outward and upward into the mine opening (Figure 1). As the underlying materials fail, the load supported by the coal pillar may be transferred to adjacent pillars. If these are marginally stable, they too may become overloaded and push into the floor. Thus, floor heave can spread through a large portion of the mine in a progressive manner. As the pillars push into the floor, differential movement and flexure of the roof strata may cause them to weaken and fail, resulting in subsidence of the ground surface above the mine. This paper describes the problem as it was manifested in the Zeigler Coal Company No. 5 and Murdock room and pillar coal mines near Murdock, Illinois, and reports the results of a U. S. Bureau of Mines- sponsored study conducted by the University of Missouri-Rolla. During the course of the study, floor heave in the two mines hindered the transportation of men, machines, and coal to and from the working mine-face, interrupted ventilation plans, drastically increased roadway maintenance costs, intensified safety and strata control problems, destroyed large pieces of equipment, and, several times, pre- vented access to otherwise minable coal resources. The ultimate objective of the study was to develop one or more simple procedures to allow detection of a potential floor heave problem during the exploration phase of mine design--before initiation of production mining.